Activity of the anticonvulsant lacosamide in experimental and human epilepsy via selective effects on slow Na+ channel inactivation. (19th November 2016) - Holtkamp, Dominik; Opitz, Thoralf; Niespodziany, Isabelle; Wolff, Christian; Beck, Heinz
Summary: Objective: In human epilepsy, pharmacoresistance to antiepileptic drug therapy is a major problem affecting ~30% of patients with epilepsy. Many classical antiepileptic drugs target voltage‐gated sodium channels, and their potent activity in inhibiting high‐frequency firing has been attributed to their strong use‐dependent blocking action. In chronic epilepsy, a loss of use‐dependent block has emerged as a potential cellular mechanism of pharmacoresistance for anticonvulsants acting on voltage‐gated sodium channels. The anticonvulsant drug lacosamide (LCM) also targets sodium channels, but has been shown to preferentially affect sodium channel slow inactivation processes, in contrast to most other anticonvulsants. Methods: We used whole‐cell voltage clamp recordings in acutely isolated cells to investigate the effects of LCM on transient Na + currents. Furthermore, we used whole‐cell current clamp recordings to assess effects on repetitive action potential firing in hippocampal slices. Results: We show here that LCM exerts its effects primarily via shifting the slow inactivation voltage dependence to more hyperpolarized potentials in hippocampal dentate granule cells from control and epileptic rats, and from patients with epilepsy. It is important to note that this activity of LCM was maintained in chronic experimental and human epilepsy. Furthermore, we demonstrate that the efficacy of LCM in inhibiting high‐frequency firing is undiminished in chronic experimental and human epilepsy. Significance: Taken together, these results show that LCM exhibits maintained efficacy in chronic epilepsy, in contrast to conventional use‐dependent sodium channel blockers such as carbamazepine. They also establish that targeting slow inactivation may be a promising strategy for overcoming target mechanisms of pharmacoresistance.